Inside out and outside in: How the COVID-19 pandemic affects self-disclosure on social media. (December 2020) - Nabity-Grover, Teagen; Cheung, Christy M.K.; Thatcher, Jason Bennett
Highlights: People engage in self-disclosure on social media to stay connected with others during the pandemic. We observe a shift in which disclosures serve the public good and which are considered socially inappropriate. We propose using the self-focus and other-focus perspectives to explain pandemic-related self-disclosure on social media. We present a research agenda and discuss practical insights. Abstract: As social distancing and lockdown orders grew more pervasive, individuals increasingly turned to social media for support, entertainment, and connection to others. We posit that global health emergencies - specifically, the COVID-19 pandemic - change how and what individuals self-disclose on social media. We argue that IS research needs to consider how privacy (self-focused) and social (other-focused) calculus have moved some issues outside in (caused by a shift in what is considered socially appropriate) and others inside out (caused by a shift in what information should be shared for the public good). We identify a series of directions for future research that hold potential for furthering our understanding of online self-disclosure and its factors during health emergencies.